The Microstructural Study of a Damaged Motorcycle Gear Wheel - Kováčiková, Petra; Dubec, Andrej; Kuricová, Jana (Manufacturing Technology Journal, 2021)
The main aim of this article is study the cause of gear wheel failure. This component has worked in the motorcycle gearbox. During the operation of the transmission, the gear wheel tooth was broken, which made it impossible to continue running this device. The investigation of the damaged area was focused on determining the chemical composition of the gear wheel material as well as detecting chemical changes in microlocalities close to the defective areas. The method of energy-dispersive spectroscopy was chosen for this type of analysis. Furthermore, the micropurity and microstructure of the material were evaluated by methods of optical microscopy and scanning electron microscopy. Using a thermo-emission scanning electron microscope, the fracture surface was evaluated in the mode of secondary electrons and also in the mode of backscattered electrons. In this way, the fracture surface was examined in terms of its micromorphology as well as material contrast.
Keywords: Gear wheel; Fracture surface; Chemical composition; Optical microscopy; Scanning electron microscopy